Analytics and Gaps in the Use of Digital Platforms for Mathematics Education in Uruguay - Eduardo Rodriguez Zidan; Gustavo Bentancor Biagas; Martin Solari (Revista Electrónica de Investigación Educativa)
Uruguay is known for its early and sustained incorporation of programs that foster the use of digital resources in public education. The country selected the mathematics education platform Bettermarks to support student education. This research analyzes data on access to and use of Bettermarks for mathematics education among secondary school students both before and during the COVID-19 pandemic. A descriptive and inferential statistical approach was used to analyze historical data on individual student interaction with the online learning activities. The findings revealed a notable increase in the coverage rate, rising from 22% to 49% from 2017 to 2020. Similarly, an upward trend was also observed in the activities completed by active users in 2020. The platform provided greater coverage, but no significant differences were observed in the activity rate between years. The analysis tested several hypotheses to elucidate heterogeneities in access and interaction among students using the digital resources. Statistically significant differences were observed in coverage and student activities, based on different factors.